Determination Analysis of Leading Commodity in the Melonguane National Border Strategic Area (NBSA) - Hanim, Wasifah; Prasca, Hafni Adinda; Pertiwi, Widhi Netraning; Yudawisastra, Helin Garlinia; Sugiartiningsih, Sugiartiningsih (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2023)
Border areas are the gateway for a country;generally, it is an underdeveloped area. This study aims to develop the economy based on only commodities in the National Strategic Activity Center (NSA) Melongguane, Kepulauan Talaud Regency, North Sulawesi Province. This study uses qualitative and quantitative approaches. The qualitative approach is based on the policy formulation of the North Sulawesi Provincial government and the Kepulauan Talaud Regency, namely the Regional Spatial Planning (RTRW) document. While the quantitative method with the Location Quotient (LQ) analysis. Based on the North Sulawesi Provincial Spatial Planning (RTRW) document shows that the leading commodities at the Melongguane National Strategic Activity Center (NSA) are Nutmeg, Coconut, Clove, and Tuna-Skipjack-cob. The Location Quotient (LQ) analysis shows that the sub-districts with potential nutmeg commodities are Kabaruan and Damau sub-districts. At the same time, the potential locations for developing Tuna-Skipjack-cob are Nanusa and Miangas Districts.